Study on the Deformation Measurement of the Cast-In-Place Large-Diameter Pile Using Fiber Bragg Grating Sensors - Gao, Lei; Yang, Kai; Chen, Xiaorui; Yu, Xiangjuan (Sensors (Basel, Switzerland), 2017)
Compared with conventional piles such as the circle pile, the cast-in-place large-diameter pile (PCC pile) has many advantages: the lateral area of PCC pile is larger and the bearing capacity of PCC pile is higher. It is more cost-effective than other piles such as square pile under the same condition. The deformation of the PCC pile is very important for its application. In order to obtain the deformation of the PCC pile, a new type of quasi-distributed optical fiber sensing technology named a fiber Bragg grating (FBG) is used to monitor the deformation of the PCC pile. The PCC model pile is made, the packaging process of the PCC model pile and the layout of fiber sensors are designed, and the strains of the PCC model pile based on FBG sensors are monitored. The strain of the PCC pile is analyzed by the static load test. The results show that FBG technology is successfully applied for monitoring the deformation of the PCC pile, the monitoring data is more useful for the PCC pile. It will provide a reference for the engineering applications.